Prenatal diagnosis of beta-thalassaemia by fetal red cell concentration with anti-AB serum. Issue 5 (October 1979) - Furbetta, M; Valenti, C; Ximenes, A; Angius, A; Tuveri, T; Fioretti, P; Cao, A
Abstract : Prenatal diagnosis by globin chain synthesis analysis on fetal blood samples obtained by placental aspiration was performed in two pregnancies at risk for beta-thalassaemia. Since both fathers had blood group AB, and both mothers had group O, fetal red cell concentration from maternal-fetal mixtures was obtained with the aid of anti-AB serum. With this approach it was possible to carry out globin chain synthesis analysis with very small amounts of fetal blood. Heterozygous and normal genotypes were ascertained and confirmed after birth.